Protocol D - Cryopreservation of sperm [Pratical guide of protocols: sperm quality] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
Cryopreservation of gametes and embryos is a key issue in the development of reproductive technologies providing the possibility to preserve genetics from rare or valuable breeds (gene banking). Long-term preservation of sperm is commonplace in cattle breeding and is being adopted in aquaculture. The progressive interest in the application of cryopreservation to aquaculture has revealed how useful this method could be in the management of fish reproduction, and moreso when it is combined with other reproductive technologies. Some of the applications, in use or under development, are: storage of sperm for handling routine in those species requiring artificial insemination (salmonids, turbot); crossbreeding programming independently of the maturation period or availability of breeders; utilization of all the sperm from species or individuals with a large production; increase of the fertile life of the individual; hybridization between species with different maturation periods... However, sperm freezing causes cellular damage and reduces sperm quality and fertility post-thaw, so careful protocols have to be developed to minimize fertility loss. In this Protocol, sea bass sperm is cryopreserved in liquid nitrogen (LN). After freezing/thawing sperm quality is assessed and compared with that of fresh sperm. Motility is evaluated following Protocol D and the percentage of viable and non-viable cells is established using fluorescent probes.